Fundamentals of Early Linguistic Literacy of Preschool Children (Annual of the Faculty of Philosophy in Skopje, 2017)
The process of linguistic literacy of children has crucial importance in relation to the overall learning and advancement. This is a complex and lengthy process, which in our context, in its most elementary form, takes a place within the first educational cycle. Contrary to traditional beliefs, nowadays modern linguistic concepts of early literacy are being built, which is increasingly treated as a holistic process of specific skills that form the basis of a language. The basic strategy of this concept is “learning everything” “through everything ” (in the meaning of individual language skills) by using different activities mixed with elements ofplay and informality. One of the basic principles of this concept is development (of cognitive, emotional and social components), progressiveness and individualization at the “input ”, through the process itself, by monitoring the progress and micro-methodic modeling adapted to the individual needs, and at the “output” when everyone reaches their maximum in their own development. These are serious and complex requirements and priorities adopted at the theoretical level, and they are occasionally implemented in the daily practice. This raises the issue about ways of educational compensation in the direction of modern strategies to become daily teaching routine.Children in preschool age should be put in many situations in which they hear, write, read and speak. Early linguistic literacy has a global importance and it is an integral part of the overall development process, but also its foundation, since without developed language skills, the learning process is almost impossible. On the other hand, this process of acquiring linguistic competences is a process of continuous improvement, and not just a process of realization of certain primary objectives, programme anticipated.
Keywords: EARLY LINGUISTIC LITERACY; LANGUAGE SKILLS; READING; WRITING